2021
DOI: 10.1111/jhn.12954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal protein intake during pregnancy on autoimmune thyroiditis in pregnant women with mild iodine deficiency

Abstract: Background: Iodine and animal protein may affect thyroid function. In the present study, we explored the association between animal protein intake and thyroid antibody status in pregnant women following universal salt iodisation. Methods: Pregnant women were enrolled using a multistage, stratified random sampling method in Shanghai. In total, 4646 eligible women were interviewed in person. We used a validated food frequency questionnaire and food composition tables to calculate the daily intakes of protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Autoimmune thyroiditis is present in 20% of women of childbearing age and, even when there is no evidence of thyroid dysfunction, it has been associated with impaired fetal brain development and greater risk of miscarriage and preterm birth. A study by Wang et al 10 found that there was a relationship between diet and severity of autoimmune thyroiditis in pregnancy. Women with mild iodine deficiency were protected from high anti‐thyroid antibody concentrations by higher intakes of animal protein.…”
Section: Nutrition and The Management Of Specific Conditionsmentioning
confidence: 99%
“…Autoimmune thyroiditis is present in 20% of women of childbearing age and, even when there is no evidence of thyroid dysfunction, it has been associated with impaired fetal brain development and greater risk of miscarriage and preterm birth. A study by Wang et al 10 found that there was a relationship between diet and severity of autoimmune thyroiditis in pregnancy. Women with mild iodine deficiency were protected from high anti‐thyroid antibody concentrations by higher intakes of animal protein.…”
Section: Nutrition and The Management Of Specific Conditionsmentioning
confidence: 99%